PROCEEDINGS ON CHALLENGING THE DECISION OF THE ARBITRATION COURT - Кhakberdiev Abdumurad Abusaidovich (Galaxy International Interdisciplinary Research Journal, 2023)
In the conditions of modernization and reform of our country, the ongoing reforms in the law enforcement and judicial-legal spheres are aimed primarily at the comprehensive protection of human rights, freedoms and legitimate interests. Providing the State with the role of the main reformer, ensuring the rule of law, and conducting a strong social policy represent reforms that are being implemented gradually and gradually. At the same time, it should be noted that at present, in addition to competent courts, arbitration courts face various problems when considering a number of cases on civil and economic disputes. The article analyzes the proceedings in cases of challenging the decision of the arbitration court and develops appropriate proposals.